Asia Pacific journal on computational engineering - Vietnamese-German University (Springer-Verlag, GmbH, 2014)
"The Asia Pacific Journal on Computational Engineering (APJCEN) is an international multidisciplinary peer-reviewed publication devoted to disseminating research in and development of theoretical and applied mechanics. APJCEN will be a forum for researchers to present their original work and scholarly reviews of solid mechanics, fluid mechanics, structural mechanics, material modeling, multi-physics and thermodynamics with significant computational components. The journal will adopt a multidisciplinary approach to link physical, experimental, and mechanics as applied to the development of and practice in computational engineering. The journal is committed to providing comprehensive and innovative techniques in computational engineering."
Keywords: Engineering mathematics : Periodicals; Engineering : Data processing : Periodicals; Mechanics, Applied : Periodicals; Engineering : Data processing; Engineering mathematics; Mechanics, Applied; Applied Mathematics